1996
DOI: 10.1002/(sici)1097-0231(19960315)10:4<459::aid-rcm501>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mass Spectrometric Characteristics of Peptides and Peptoids

Abstract: The collision-induced dissociation (CID) spectra of the [M+H]+ ions of a pentapeptide and the corresponding peptoid and retropeptoid have been compared. The spectra of the peptide and peptoid both exhibit B- and Y"-type sequence ions at identical m/z values. In contrast to the peptide, the [M+H]+ ion of the peptoid and all sequence ions containing an N-substituted glycine derivative corresponding to a tyrosine amino acid residue can easily lose a C7H6O molecule in a charge-remote fragmentation process. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…Therefore, MS/MS was used to obtain more detailed structural information. In the case of peptides and peptoids this method can be used for sequencing, because the fragments that result from CID of the protonated molecular ion [M + H] + are directly related to the peptide or peptoid sequence 23, 24. The proposed nomenclature for the sequence ions of peptoids corresponds to that of peptides (Roepfstorff nomenclature25) and could therefore be used here also for peptoid–peptide hybrids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MS/MS was used to obtain more detailed structural information. In the case of peptides and peptoids this method can be used for sequencing, because the fragments that result from CID of the protonated molecular ion [M + H] + are directly related to the peptide or peptoid sequence 23, 24. The proposed nomenclature for the sequence ions of peptoids corresponds to that of peptides (Roepfstorff nomenclature25) and could therefore be used here also for peptoid–peptide hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…This flexibility results from rotation about the tertiary amide bond, which is much less difficult than rotation about a secondary amide bond in (non‐proline‐containing) peptides. Two earlier reports from our laboratories showed that mass spectrometry can play a key role in the unambiguous characterization of peptoids 23, 24. Using the technique of fast atom bombardment ionization combined with high‐energy collision‐induced dissociation (CID) tandem mass spectrometry (MS/MS), spectra of the [M + H] + ions of peptoids and isomeric peptides were compared and found to differ in their relative abundances of Y″‐ and B‐type fragment ions.…”
Section: Introductionmentioning
confidence: 99%
“…Although CA of proton or metal ion-charged peptides generates ions from charge-remote fragmentation and provides some structural information (Johnson et al, 1987;Johnson, Martin & Biemann, 1988;Ishidawa et al, 1994;Summer®eld et al, 1995;Boutin et al, 1996;Heerma et al, 1996), ions from charge-driven chemistry are also formed because the location of the charge on the peptide chain is mobile and dif®cult to predict. Although the resulting spectra are not dif®cult to predict, spectra produced by a single charge-remote process may be simpler to interpret.…”
Section: G Peptidesmentioning
confidence: 99%
“…Peptoids fragment in a manner similar to that of peptides under CID conditions [41,42,44,47]. The main fragment ions observed correspond to the dissociation of the amide bonds of the peptoid backbone, which produce B-and Y-series ions (following the Roepstorff and Fohlman nomenclature [49]).…”
Section: Nomenclature Of Peptoid Fragment Ionsmentioning
confidence: 99%
“…Tandem mass spectrometry (MS/MS) techniques coupled with either electrospray ionization (ESI) or matrix-assisted laser desorption/ionization (MALDI) are now routinely used for peptide and protein sequencing [34][35][36][37]. These tandem mass spectrometry based techniques have also shown promise as the method of choice for peptoid sequencing [29,[38][39][40][41][42][43][44][45][46]. We have previously studied the fragmentation patterns of a group of protonated and alkali-metallated peptoids under collision-induced dissociation (CID) as well as under electron capture dissociation (ECD) conditions [47,48].…”
mentioning
confidence: 99%